Leveraging intellectual capital and knowledge management to drive innovation and organizational performance - Suparwadi; Mochammad Al Musadieq; Muhammad Faisal Riza; Benny Hutahayan (International Journal of Engineering Business Management)
In the evolving landscape of higher education, identifying key drivers of organizational performance is crucial. This study investigates the impact of intellectual capital on knowledge management and innovation and how these factors collectively enhance organizational performance. Conducted among top leaders at 21 state universities in Indonesia, this quantitative research used structured questionnaires validated by prior studies. The high response rate strengthens the reliability of findings analyzed using SPSS for descriptive statistics and Structural Equation Modeling (SEM) with SmartPLS 3.0 for hypothesis testing. The results indicate intellectual capital significantly influences knowledge management and innovation, which in turn positively affect organizational performance. Intellectual capital enhances both knowledge management and organizational performance, while effective knowledge management fosters innovation, further contributing to improved performance. The novelty of this research lies in its comprehensive integration of intellectual capital, knowledge management, and innovation within the context of higher education, providing empirical evidence of their interconnectedness and collective impact on organizational performance, which has been largely unexplored in previous studies. This study’s practical implications encourage strategic investments in intellectual capital and knowledge management, ultimately contributing to improved organizational performance and providing valuable insights for policy and decision-making in the higher education sector.